The Secondary School Students’ Usage of English Learning Websites to Self-Correct Writing Errors - Alia Nur Dodgson Bt Tariq; Masdinah Alauyah Md. Yusof (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2016)
Corrective feedback (CF) is an inevitable teaching strategy carried out by educators, especially in an English Language classroom. Past studies have shown that corrective feedback is effective; however, indirect corrective feedback seems to have a variety of issues that has caused it to be unsuccessful. Some studies found that one of the setbacks of indirect corrective feedback is students are still having difficulties in dealing with and learning from the indirect corrective feedback itself. Students could not rectify their errors as they do not have sufficient linguistic knowledge to facilitate them, especially when they have to deal with complex linguistic errors all by themselves. Hence, this research was carried out to address this problem via the utilization of the English Language learning websites as the reference materials for the students to deal with complex linguistic errors. It was hoped that the students would be able to deal with indirect corrective feedback and successfully self-correct their errors. The qualitative research approach was employed in this research, where participants recorded their usage of the English Language learning websites in a logbook. Five randomly selected participants were interviewed to obtain a more comprehensive understanding of their experience, feedback and comments. The results showed that there were positive reactions and comments which indicated that the use of the English Language learning websites has been successful in assisting the participants in dealing with indirect corrective feedback and in doing self-correction. However, there were also negative reactions to be taken into account. Thus, this presentation will highlight some insights from the research.